El método cooperativo en el Aprendizaje Cognitivo y Procedimental del idioma inglés de los estudiantes del 3er grado del nivel primario de la Institución Educativa Nº 0005 - Morales - 2011 - Reyes Culqui, Juan Miguel (2013)
The title of the following research Cooperative Method in Cognitive and Procedural Leaming of English Language for Students of the 3th Grade Elementary Level of Educational lnstitution Nº 0005 - from Morales district. To develop this investigation the following objective was considerad: to demonstrate the cooperative method in the students of third grade of elementary level of the educational institution Nº 0005 - Morales to improve the cognitive and procedural leaming of the English language, in 2011 . With the purpose to achieve our hypothesis is as it follows; The cooperative method has a significant influence in the cognitiva and procedurat learning of the English uages of the students of the third grade of the etementary tevet of the educational institution N° 0005 - Morales. In order to demonstrate the hypothesis, an experimental with quasi-experimental design research was developed and apptied, having a Pre-Test and a Post-Test as instruments of control. Twenty two (22) students, from the third grade · of the . etementary level, of the educational institution Nº 0005 - Morales, were the sample, which twenty two (22) students of third grade were "the experimental group". This group of students had a test before and after the experiment. The data analysis of the Pre-Test anda Post-Test of the experimental group attowed us demonstrate our hypothesis (H¡). There is a significant difference between the average of the seores of the pre and post- test of the experimental group from seven (7) to seventeen (17). The analysis and the interpretation of the resutts have been gotten to establish that the experimentation of the cooperativa method have been improved significantly in the cognitive and procedural learning of the English Language, in the students of the third grade of mentary level, of the educationat institution Nº 0005 - Morales, in 2011 .